Relação entre book-tax differences e os honorários de auditoria das companhias abertas brasileiras - Ávila, Jéssica Rayse de Melo Silva (2016)
The adoption of International Financial Reporting Standards (IFRS) presented as basic prerequisite the dissociation of tax rules from financial rules, which provided managers with the possibility to make more accounting decisions, representing that a proper scenario for the increase of total difference between accounting income and taxable income (Book-tax Difference BTD). The BTD is considered a factor capable of increasing risks evaluation and auditor\'s efforts, which raises fees as form o compensation. Defined in terms of objective, this research aims at checking whether exists relation between BTD and audit fees that were paid by Brazilian listed companies. The sample of this research is compounded by 347 Brazilian listed companies which traded stocks in BM&FBovespa from 2010 to 2014. All BTD classifications were tested: total, temporary, permanent, abnormal, normal, positive and negative. As statistical procedures, descriptive statistics, bivariate correlation and panel modeling were used. Except for the abnormal difference between accounting income and taxable income (BTDAN), all kinds of BTD presented positive and significant correlation with audit fees, enabling them to be considered useful methods for their comprehension. It also became evident that in each 1% of increase in positive difference between accounting income and taxable income there is a rise of 8,8% on audit fees, suggesting that auditors assign higher efforts and loss risks in the presence of that one.